Making Time and Space for Art: An Examination of an Artist-in-Residence Within a Postsecondary Art Education Program - Shields, Alison Lea; Percy, Ingrid Mary; Vander Meer-Chassé, Teresa (The Canadian Review of Art Education, 2021)
This article examines the process and impact of an artist-in-residence program in Art Education at the University of Victoria. After an open call to artists, contemporary Upper Tanana visual artist, Teresa Vander Meer-Chassé, member of the White River First Nation of Beaver Creek, Yukon and Alaska was selected as the inaugural artist-in-residence. Through research-creation and qualitative methods this research examines the artist’s artistic process and the impact of an artist-in-residence on students’ and faculty’s perception of artistic practice and their experience working with an artist-in-residence within a post-secondary space of learning. Through photographic documentation, reflections and interviews by participants, the article examines ways the artist-in-residence enriched student and faculty learning in a Faculty of Education. Cet article s’intéresse au processus et à l’impact d’un programme d’artiste en résidence dans le domaine de l’enseignement des arts à l’Université de Victoria. Suite à une audition ouverte d’artistes, l’artiste visuelle contemporaine du Haut Tanana Teresa Vander Meer-Chassé, membre de la Première Nation de White River de Beaver Creek, du Yukon et de l’Alaska, a été choisie artiste-résidente inaugurale. La présente recherche utilise des méthodes quantitatives et de recherche-création pour étudier la démarche artistique de l’artiste et l’impact d’une artiste-résidente sur la perception de la pratique artistique chez les étudiants et le corps enseignant. On y analyse aussi l’impact de collaborer avec une artiste-résidente en milieu d’apprentissage postsecondaire. Documentation photographique, réflexions et entrevues des participant.e.s sont mises à profit pour déterminer de quelles façons l’artiste- résidente a enrichi l’apprentissage étudiant et du corps enseignant au sein de la Faculté d’éducation.